(3JaSjQ GdTjN CHj SYjO GdMfajs - (3GdfjSGHhQj GdMfaj, CHh SYjO, YHO Gddg Hf eMeO Hf EHQGgje, J (B407 (3g`s
(3ChdgG (B:s
(3ShQI GdaGJMI GdcJGH hSHY BjI heOfjI GYde Gf aj gPg GdShQI cdGeG aj hLhg cKjQI CMOgG aj aVGFHgG hGdKGfj aj YOO BjGJgG hcdeGJgG hMQhagG hGdETGQI ajgG hGdKGdK aj fRhdgG hGdQGHY aj HSGWgG (B...s
(3BNQgG (B:s
(3ShQI GdfGS hgj SJ BjGJ HSe Gddg GdQMef GdQMje hHg fSJYjf bd CYhP HQH GdfGS Edi BNQ GdShQI bGd CHh SYjO GdMfaj GYde Cf aj gPg GdShQI cdGeG ef hLhg NeSI CMOgG (B...(3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2\272s
(3eYLe GdeDdajf (B2\272s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs